The Theoretical and Practical Significance of the Religious and Sufi views Found in the Life and Works of Mirbobo Naqshbandi Today (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article highlights that the Naqshbandi Sufi order has gone through a significant historical period from its inception to the present day. It discusses how the Naqshbandi order developed further, spread among many people, and attracted a growing number of followers. The progress of the order was, of course, greatly contributed to by its spiritual leaders, representatives, and Sufi theorists.